Casearia sylvestris essential oil and its fractions inhibit Candida albicans ABC transporters related to multidrug resistance (MDR) - Domingos,Levy Tenorio Sousa (2021)
Abstract ABC transporters constitute a superfamily of transmembrane proteins that act mediating the translocation of several substrates across the membrane, using the energy of ATP hydrolysis. This mechanism of unrelated substrates efflux (multidrug resistance) has been associated with several diseases and it is a problem in chemotherapy efficacy. Nowadays, approximately 25% of the prescription drugs in the world are derived from plants. Casearia sylvestris is commonly found in the Americas and different parts of this plant are popularly used to treat several diseases. Previous studies have also confirmed the biological activities of C. sylvestris, such as anti-tumor, anti-leishmania, and antifungal properties. Then, the propose of this study was demonstrate that fraction 1-6 of C. sylvestris, essential oil, was able to reverse the fluconazole resistance phenotype in the Saccharomyces cerevisiae model mediated by the heterologous protein CaCdr2p from Candida albicans. The MIC value of fraction 1-6 combined with fluconazole in the checkerboard assay decreased approximately 4-fold, suggesting a synergistic effect. In addition, fraction 1-6 increased intracellular rhodamine 6G accumulation from 17% to 49% in the presence of glucose. Data indicate that C. sylvestris fraction 1-6 is a potential reverser of the fluconazole resistance phenotype.